IDULFITRI MARKETING - Agus Hasan Pura A (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
Marketing of led fitr is a seasonal marketing. More than 200 million people in Indonesia are moslem and as a moslem they have an obligation to do fasting in ramadhan month before the led fitr. Unfortunately, moslems in lndonesia have mixed the value of lslam with their tradition such as